2011
DOI: 10.1159/000327546
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Coupling of Vitamin D3 to the Major Cat Allergen Fel d 1 Improves the Effects of Allergen-Specific Immunotherapy in a Mouse Model for Cat Allergy

Abstract: Background: Allergen-specific immunotherapy (SIT) is currently the only curative treatment for allergy but the treatment needs to be improved. We hypothesize that covalent coupling of immunomodulating vitamin D3 to the major cat allergen Fel d 1 can enhance the beneficial effects of SIT to cat allergy. Methods: We treated mice sensitized to Fel d 1 with subcutaneous injections of two doses of recombinant Fel d 1 coupled to 1α,25-dihydroxyvitamin D3 (rFel d 1:VD3) and compared to treatment with the same doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 100 publications
3
27
0
Order By: Relevance
“…However, our findings are consistent with previous reports in mice showing the effects of SIT in the presence of calcitriol including the reduction of the Th2 cytokine IL-13 in the BALF (19,36). Because IL-13 expression is critical for the induction of AHR (38), the reduced IL-13 levels might at least partly explain the ameliorated AHR in D-SIT-treated mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our findings are consistent with previous reports in mice showing the effects of SIT in the presence of calcitriol including the reduction of the Th2 cytokine IL-13 in the BALF (19,36). Because IL-13 expression is critical for the induction of AHR (38), the reduced IL-13 levels might at least partly explain the ameliorated AHR in D-SIT-treated mice.…”
Section: Discussionsupporting
confidence: 93%
“…In previous reports on murine models, SIT was started on days 2-14 after sensitization (in this study: day 21) and performed daily or alternating days (in this study: weekly intervals). Also, lung function analysis was determined 1-2 wk after SIT (19,36) and thus earlier than in this study (6 wk) (Fig. 3A).…”
Section: Discussionmentioning
confidence: 86%
“…It was also shown that the coupling to virus-like particles reduced the allergenic activity of the major cat allergen Fel d 1 [66]. Using Fel d 1 as a model allergen in a murine model of cat allergy, it was also demonstrated that covalent coupling of vitamin D3 to Fel d 1 improved the effects of SCIT [67].…”
Section: Cpg-conjugated and Other Coupled Allergensmentioning
confidence: 96%
“…1,25-DihydrovitaminD3 has been shown to increase regulatory T-cell responses by affecting dendritic cells for their tolerogenic properties. In a mouse model for cat allergy, vaccine containing rFel d 1 covalently coupled to VitD3 was tested [46], showing superiority to rFel d 1 only.…”
Section: The Fusion Of Allergens To Immune Modifiers and Peptide Carrmentioning
confidence: 99%